Study Group on Reforms in State Public Sector Undertakings Final Report Volume I - Planning Commission (Planning Commission, 2002)
Public sector reforms occupy a vital place in the process of second-generation reforms. Public sector reforms are generally considered synonymous with reforms in the central public enterprises. The fact that State PSUs are as important as the central public enterprises in terms of investment, manpower and efficiency is sometimes lost sight of. The financial performance of these enterprises has a direct bearing on the health of State finances that are not in a good shape at present. There has been no comprehensive study on the State PSUs during the recent times.
Planning Commission, Government of India